2020
DOI: 10.15511/tjtfp.20.00449
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors and problems of a medical school students’ related to distance education in pandemic medical education in the pandemic process

Abstract: Introduction and Aim: In a medical school, to determine whether students have the necessary infrastructure for distance education, students’ access to educational materials, the concerns and expectations of students about the process. Methods: First, second, third, fourth and fifth-year students, continue through distance education in the pandemic process in Cumhuriyet University Medical School, were included in the study. 336 students volunteered to participate in this descriptive research. The data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…8 In a similar study conducted by Karagöz et alwith medical faculty students, 82.1% of the participants stated that they studied less than the old working order in the distance education process, while 7.1% of the students did not change and 10.7% more it was found to be studying. 9 Similarly, in the present study, 54.7% of the participants stated that the study time decreased. In another study conducted in Pakistan, 71.4% of the participants disagreed with the idea that online education is more motivating than face-to-face education.…”
Section: Discussionsupporting
confidence: 73%
“…8 In a similar study conducted by Karagöz et alwith medical faculty students, 82.1% of the participants stated that they studied less than the old working order in the distance education process, while 7.1% of the students did not change and 10.7% more it was found to be studying. 9 Similarly, in the present study, 54.7% of the participants stated that the study time decreased. In another study conducted in Pakistan, 71.4% of the participants disagreed with the idea that online education is more motivating than face-to-face education.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, strong systematic infrastructure increases the rates of following courses and affects satisfaction from distance education (25). In a study conducted y Karag z et al, it was concluded that multimedia elements should be increased in materials uploaded to distance education system, educational materials should be made more comprehensible and materials in the system should have a specific order (11). n one study, Saltür and Güng r emphasized the significance of removing prejudices towards distance education and being open to innovations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the problems that occur with these technological tools, it is also possible for individuals to experience individual problems. Issues such as decrease in student motivation, decreased attention, anxiety, the fact that online education content does not allow applied courses, lack of communication and experiencing difficulty in understanding goals also pose obstacles to online education (11,12). However, since social distance may continue in the future, increasing the quality of online education is very important (2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are worried about the decrease in the desire to study, how the educational results will be evaluated, and the decrease in their grades. 12,13,15 Although both clinical and preclinical students are afraid of infecting themselves and their environment with Covid 19 16 , the majority of students feel the lack of clinical practice and want to return to the clinical environment. 11,15,17 According to the common results of the publications in which students' interest in the e-learning method was investigated after the Covid 19 pandemic, students prefer the hybrid learning method, which combines classical learning and e-learning 7,9,14 and demand that multimedia elements be increased.…”
mentioning
confidence: 99%
“…12,13,15 Although both clinical and preclinical students are afraid of infecting themselves and their environment with Covid 19 16 , the majority of students feel the lack of clinical practice and want to return to the clinical environment. 11,15,17 According to the common results of the publications in which students' interest in the e-learning method was investigated after the Covid 19 pandemic, students prefer the hybrid learning method, which combines classical learning and e-learning 7,9,14 and demand that multimedia elements be increased. 15 Students who think that clinical skills training has been negatively affected during the pandemic have self-confidence problems in starting an independent practice after graduation, so they want to take postgraduate courses in the future.…”
mentioning
confidence: 99%